Learning for Democracy - Hoggan-Kloubert, Tetyana. author. aut Link
XV, 259 p. 3 illus., 2 illus. in color.
Keywords: This book offers a framework for adult civic learning, positioning democracy not merely as a form of government, but as an overarching way of living together, where citizens understand and support essential principles of democracy. These principles are often in conflict with one another, meaning that citizens must negotiate the tensions that arise between them. Highlighting the principles of Autonomy and Solidarity, and Rationality and Pluralism, the authors explore the importance and dangers of each of them for democracy. This framework for adult civic learning explores the implications of these competing principles for civic life, and therefore civic learning and adult education practice. The book will serve as a valuable resource for educators, policymakers and individuals who are interested in promoting adult civic learning and ensuring the growth and vitality of democracy. Tetyana Hoggan-Kloubert is Akademische Rätin (Associate Professor) of Adult and Continuing Education at the University of Augsburg, Germany. Chad Hoggan is Professor of Adult & Lifelong Education at North Carolina State University, USA.